Unbalance and resonance elimination with active bearings on a Jeffcott Rotor. (15th February 2017) - Heindel, Stefan; Becker, Fabian; Rinderknecht, Stephan
Abstract: In this contribution we have proven theoretically and practically that active bearings are able to eliminate both bearing forces and the resonance of a Jeffcott Rotor system. Active bearings can displace a rotor such that its center of mass always stays in the rotational center. The proposed collocated controller is able to keep this state at any rotational speed, leading to an elimination of bearing forces and resonances. We analytically demonstrated that the closed-loop system is always stable, even without knowledge of the rotor's properties. The generalization of the proposed control approach for force-free operation either using displacement or force actuators enables its use for all kinds of active bearings. Moreover, the control approach allows a real time estimation of the rotor's eccentricity. The low parameter count and the unproblematic stability behavior qualify the controller for many applications. Abstract : Graphical abstract: Abstract : Highlights: Force and resonance elimination with active bearings for Jeffcott Rotors. Closed-form solution and proven stability. Generalized approach, suitable for force and displacement actuators. Comprehensive explanation without transfer functions. Approach proven in experiment.